2020
DOI: 10.1038/s41427-020-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

An injectable photopolymerized hydrogel with antimicrobial and biocompatible properties for infected skin regeneration

Abstract: Currently, wound infection is an important health problem for the public. Wound infection can not only hinder healing but it can also lead to serious complications. Injectable wound dressings with biocompatible and antibacterial properties can promote wound healing during skin infections and reduce antibiotic use. Here, we used glycidyl methacrylate (GMA) to modify ε-polylysine (ε-PL) and γ-poly(glutamic acid) (γ-PGA) to produce ε-polylysine-glycidyl methacrylate (ε-PL-GMA) and γ-poly(glutamic acid)-glycidyl m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 40 publications
1
76
0
Order By: Relevance
“…Using the partial-thickness burn injury model, followed by infection with a clinical strain of a multidrug-resistant gram-negative A. baumannii, Khan et al, demonstrate the ability of the newly developed EPL-hydrogel to significantly reduce in-vivo biofilms in burn wounds (Fig 2) which is most likely attributed to the action of both EPL and function of reactive oxygen species (ROS) and hydrogen peroxide (H2O2) byproducts of catechol oxidation. Indeed, this agrees with previous studies which have also described the use of injectable EPL nanocomposite hydrogel to combat infection and promote tissue healing and regeneration in-vivo [15] however exact mechanisms of actions in burn wounds are yet to be determined. The tunable functionalities of the EPL-catechol biomaterial make it a promising product for future investigation in biomedical applications.…”
supporting
confidence: 91%
“…Using the partial-thickness burn injury model, followed by infection with a clinical strain of a multidrug-resistant gram-negative A. baumannii, Khan et al, demonstrate the ability of the newly developed EPL-hydrogel to significantly reduce in-vivo biofilms in burn wounds (Fig 2) which is most likely attributed to the action of both EPL and function of reactive oxygen species (ROS) and hydrogen peroxide (H2O2) byproducts of catechol oxidation. Indeed, this agrees with previous studies which have also described the use of injectable EPL nanocomposite hydrogel to combat infection and promote tissue healing and regeneration in-vivo [15] however exact mechanisms of actions in burn wounds are yet to be determined. The tunable functionalities of the EPL-catechol biomaterial make it a promising product for future investigation in biomedical applications.…”
supporting
confidence: 91%
“…LAP in cell culture medium is exposed to the in vitro equivalent of the apical membrane of collecting duct cells. Additionally, the use of this cell model would expand the scope to technologies that could directly contact native tissue, such as tissue adhesives, injectable wound dressings, or hand-held extrusion printers for bioprinting during surgery [ 26 , 27 , 28 ]. Therefore, the objectives of this study were to: (1) characterize light exposure conditions typical of bioprinters, using LEDs as a light source; (2) assess whether LAP with concurrent light exposure enhances cytotoxicity in confluent M-1 cells; and (3) determine if exaggerated exposure conditions associated with high cytotoxicity are mutagenic using bacterial reverse mutation assays.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In a genome-wide association study, SARS-CoV-2 was found to have a similarity of 79.5% in genomic sequence to the SARS coronavirus and to be 96% homologous to that of a bat-derived coronavirus, suggesting that bats are the main source of transmission of SARS-CoV-2. 16 Aside from bats, pangolins have been regarded as a possible source of SARS-CoV-2 transmission as well. Lam et al discovered that pangolin-derived coronaviruses were closely associated with two sublineages of SARS-CoV-2-related coronaviruses through metagenomic sequencing.…”
Section: Virus Reservoirs and Its Transmissionmentioning
confidence: 99%